1991
DOI: 10.1210/endo-129-3-1363
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Unsaturated Fatty Acids on the Binding of Glucocorticoids to Rat Liver Glucocorticoid Receptors*

Abstract: Binding of the synthetic glucocorticoid dexamethasone to the rat liver cytosol glucocorticoid receptor was inhibited by physiological concentrations of nonesterified fatty acids as a function of increasing dose, degree of unsaturation, and chain length of the fatty acid. Polyunsaturated fatty acids were the most potent inhibitors. Scatchard analysis and Line-weaver-Burk plots of the binding data revealed that both the association constants and number of binding sites decreased and that polyunsaturated fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…In addition, they raise the possibility of an additive or synergistic inhibitory effect of GLA with tamoxifen via enhanced down-regulation of ER-mediated growth. Our ER data are consistent with the previously identified modulatory properties of PUFA metabolites on steroid hormone receptors in various animal tissues (Clerc-Hoffman et al, 1983;Mitsuhashi et al, 1986Mitsuhashi et al, , 1988Vallette et al, 1991). Borras and Leclercq (1992) have demonstrated a dose-dependent down-regulatory effect of n-6 PUFA metabolites on growth and ER expression in the ER ϩ breast cancer cell line MCF-7.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, they raise the possibility of an additive or synergistic inhibitory effect of GLA with tamoxifen via enhanced down-regulation of ER-mediated growth. Our ER data are consistent with the previously identified modulatory properties of PUFA metabolites on steroid hormone receptors in various animal tissues (Clerc-Hoffman et al, 1983;Mitsuhashi et al, 1986Mitsuhashi et al, , 1988Vallette et al, 1991). Borras and Leclercq (1992) have demonstrated a dose-dependent down-regulatory effect of n-6 PUFA metabolites on growth and ER expression in the ER ϩ breast cancer cell line MCF-7.…”
Section: Discussionsupporting
confidence: 92%
“…Previous kinetic studies have implicated PUFAs to bind to a separate entity on the hormone receptor to the hormone binding site, thus inhibiting subsequent hormone-ligand binding via induction of a conformational change in the receptor molecule (Hwang, 1987;Kato, 1989;Vallette et al, 1991). Vallette et al (1988) in a detailed study investigated the influence of unsaturated fatty acids on the binding of estradiol to ERs in the uterine tissue of juvenile rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, namely B max decreased and K d increased with increasing concentrations of Z,Z-TDD (Table 2). A similar pattern of inhibition has been noted in prior studies, such as those on the inhibition of dexamethasone binding to glucocorticoid receptor by docosahexaenoic acid (28) and on that of anthraniloyl-7-methylguanosine triphosphate binding to the wheat germ translation initiation factor eIFiso4E by the genome-linked protein of the turnip mosaic virus (12). This is considered to be indicative of mixedtype competitive binding between two species of li- The B max (and the S.E.…”
Section: An Assessment Of the Inhibition Pattern Of Zz-tdd For Afl-osupporting
confidence: 71%
“…Previous kinetic studies have suggested that EFAs bind to a separate entity on the hormone receptor rather than to the hormone binding site, thus inhibiting subsequent ligand binding via induction of a conformational change in the receptor molecule. 18,19,33 Vallette and colleagues have demonstrated irreversible covalent binding of oestradiol to components of the ER protein in the presence of EFAs. 34 It is possible that in the presence of GLA a similar covalent bond is formed between tamoxifen and ER with resultant attenuation of receptor activity.…”
Section: Discussionmentioning
confidence: 99%